Quantitative analysis: How annealing temperature influences recrystallization texture and grain shape in tantalum. (April 2018) - Fan, Haiyang; Liu, Shifeng; Deng, Chao; Wu, Xiaodong; Cao, Lingfei; Liu, Qing
Abstract: The recrystallization behavior of tantalum was investigated under two different annealing regimes, i.e. long-time annealing at low temperatures (LALT) and short-time annealing at high temperatures (SAHT), aiming to elucidate how annealing schedule arouses not only different texture evolution but grain shape as well. The texture and grain morphologies at each recrystallization stage were revealed by Electron Back-Scatter Diffraction (EBSD) technique. LALT was observed to enhance the {100} texture (〈100〉//ND (normal direction)) while simultaneously suppressing the {111} texture (〈111〉//ND); whereas a reverse trend of texture evolution was observed under SAHT. In terms of grain shape, different from the near-equiaxed grains introduced by LALT, SAHT resulted in lots of elongated grains with random orientations (i.e. orientations except for {111}〈uvw〉 and {100}〈uvw〉). The formation mechanism of elongated grains was established. It is anticipated that results in this study would provide guidelines for microstructural optimization of Ta sputtering targets. Graphical abstract: Highlights: How the annealing temperature influences the texture evolution in tantalum is analyzed. How the annealing temperature affects grain shapes and the formation mechanism of elongated grains are reported. The orientation-dependent recrystallization and corresponding mechanisms are revealed. A well-controlled recovery prior to recrystallization benefits a homogeneous texture and microstructure in tantalum.